1996
DOI: 10.3171/jns.1996.85.5.0793
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and radiological instability following decompressive lumbar laminectomy for degenerative spinal stenosis: a comparison of patients undergoing concomitant arthrodesis versus decompression alone

Abstract: One hundred twenty-four patients with degenerative lumbar stenosis underwent decompression with fusion (32 patients) and without fusion (92 patients) during a 30-month period between 1986 and 1988. Patient-reported satisfaction at a mean follow-up period of 5.8 years (range 4.6-6.8 years) revealed a 79% good or fair outcome and a 21% poor outcome (26 patients). Seven patients (6%) developed lumbar instability, three patients (2%) developed new stenosis at an adjacent unoperated level, and three patients (2%) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(142 citation statements)
references
References 101 publications
9
119
1
6
Order By: Relevance
“…Greater comorbidity (p = 0.014) and higher preoperative COMI (p = 0.048) were also significant predictors of a worse outcome in the multivariable model degenerative changes leading to canal compromise. Fox et al looked at a series of patients with decompression for spinal stenosis with and without fusion and reported a progression in spondylolisthesis after decompression alone in 73% of patients with LDS compared with 31% without, again demonstrating the ongoing process of instability that might be enhanced by decompression alone [4]. The findings of the present study concur with those reported by Martin et al in systematically reviewing the literature comparing different types of surgical treatment for LDS [14].…”
Section: Discussionsupporting
confidence: 87%
“…Greater comorbidity (p = 0.014) and higher preoperative COMI (p = 0.048) were also significant predictors of a worse outcome in the multivariable model degenerative changes leading to canal compromise. Fox et al looked at a series of patients with decompression for spinal stenosis with and without fusion and reported a progression in spondylolisthesis after decompression alone in 73% of patients with LDS compared with 31% without, again demonstrating the ongoing process of instability that might be enhanced by decompression alone [4]. The findings of the present study concur with those reported by Martin et al in systematically reviewing the literature comparing different types of surgical treatment for LDS [14].…”
Section: Discussionsupporting
confidence: 87%
“…However, there are many papers with class II and III evidence levels advocating concomitant spinal fusion and arthrodesis to improve outcomes and avoid late instabilities, even in patients without spondylolisthesis or spinal deformities [29][30][31][32][33][34] . It is known that when more than 30% of the articular facets are removed bilaterally, we have a greater probability of developing late instability, justifying fusion in patients subjected to large decompressive surgeries 35 .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Surgical procedures aim to decompress the nerve root emerging from the thecal sac along its course in the lateral recess. A multitude of surgical procedures for surgical decompression of symptomatic lateral recess stenosis have been described ranging from standard open laminectomies to minimally invasive decompressive techniques (14)(15)(16)(17)(18)(19)(20)(21)(22). In the current study we describe the surgical technique of endoscopic interlaminar lateral recess decompression in a small cohort of patients with unilateral symptomatic lateral recess stenosis with well-defined radiographic criteria.…”
Section: Introductionmentioning
confidence: 99%